Evaluating Education Quality For Sustainable Development: A Systematic Literature Review - Andi Rizka Ekaputri; A. Hadijah Sulfiyani A (Kilau Publishing, 2026)
This study aims to analyze the evaluation of the quality of education in the context of sustainable development by identifying themes, dimensions, indicators, evaluation approaches, and research gaps. The study is important because the increasing complexity of educational challenges in the digital and sustainability era requires a more comprehensive and integrative evaluation model to ensure equitable and high-quality education. However, previous studies on educational quality evaluation tend to be fragmented and still dominated by conventional approaches, with limited integration of sustainability, technology, and equity dimensions. This research uses a systematic literature review with bibliometric and thematic approaches. Data were collected from selected scientific articles based on clear inclusion and exclusion criteria. Validity and reliability were maintained through a systematic selection process, data filtering, and analytical consistency. Data analysis was conducted using Biblioshiny to map research publication trends and distributions, as well as VOSviewer to identify thematic structures and conceptual relationships. The results show that the quality of education is a multidimensional construct that includes pedagogical, equity, evaluative, institutional, sustainability, and technological aspects. Evaluation practices are still dominated by quantitative approaches and conventional models, although recent developments indicate a growing integration of technology-based evaluation systems. This study also identifies research gaps related to sustainability integration, technology utilization, and equity measurement, highlighting the need for a more holistic and adaptive educational quality evaluation model.